Market Risk on Bank Profitability: Evidence from Indonesian State-Owned Banks - Nagari, Monica Suprajaya Duta; Manda, Gusganda Suria (Pascasarjana STIE Amkop Makassar, 2022)
The objective of this study is to analyze the effect of market risk, as proxied by interest rate risk and foreign exchange risk, on the profitability of State-owned banks in Indonesia within the period 2013-2020. Interest rate risk is proxied by net interest margin (NIM), foreign exchange risk is proxied by net open position (NOP), and bank profitability is proxied by return on assets (ROA). Four State-owned banks were chosen as a sample by employing a saturated sampling technique. The data were processed using the SPSS 26th version by performing multiple linear regression analysis. The findings of this study discover that interest rate risk (NIM) partially has a positive and significant effect on State-owned banks’ profitability (ROA). Conversely, foreign exchange risk (NOP) partially has a negative and not significant effect on State-owned banks’ profitability (ROA). Interest rate risk (NIM) and foreign exchange risk (NOP) simultaneously have a significant impact on State-owned banks’ profitability (ROA).